Morphological redescription and population genetics of Pagastia (Pagastia) orientalis (Tshernovskij, 1949) (Diptera: Chironomidae: Diamesinae) - Semenchenko, Alexander A.; Yagodina, Viktoriia D.; Seliverstov, Nikita A.; Makarchenko, Eugenyi A. (Zootaxa, 2024)
Pagastia (P.) orientalis (Tshernovskij, 1949) is redescribed by morphology of adult male from East Palaearctic with remarks on some variability of morphological features and with consideration of population genetics of species, namely population structure and variability from 24 localities belonging to 10 groups.  Population genetic analysis of P. (P.) orientalis revealed multiple haplotypes (209 haplotypes for 213 samples) and a high level of haplotype diversity—0.999±0.001. The results of neutrality tests were significant (P<0.01) and showed negative values, which may indicate population expansion in the past. Clustering of haplotypes into haplogroups was shown, the differentiation between which is significant (P<0.001) while the gene flow was almost virtually absent, which may affect at the level of genetic diversity of a single population.